Organizational Commitment and its Relation with Social Responsibility among the Employees of College of Basic Education/University of Duhok - Jaafar Abdullah, Beshkosh (Academic Journal of Nawroz University, 2022)
This study aims to investigate about the organizational commitment and its relation with social responsibility among the employees of college of Basic Education in the University of Duhok it also aim to find out the statistical differences according to the variables of ( scientific achievement, duration of work, work position, time of work and gender). The sample of the study consisted of (73) employees. The researcher used the quantitative descriptive method in this study and used two questionnaires to collect data the first consisted of(38) items distributed on (4) axes which are( organizational loyalty, responsibility towards the work, the will of continuing the work and the believe in the work) the second questionnaire consisted of (24) items. One and independent sample T. Test was used in addition to one way annova, weighted mean, and Pearson correlation were used as statistical methods. The result showed that the employees had the characteristic of organizational commitment and social responsibility and that the variables of the study were statistically insignificant except for scientific achievement.